2014
DOI: 10.3389/fimmu.2014.00432
|View full text |Cite
|
Sign up to set email alerts
|

T Cell–Macrophage Interactions and Granuloma Formation in Vasculitis

Abstract: Granuloma formation, bringing into close proximity highly activated macrophages and T cells, is a typical event in inflammatory blood vessel diseases, and is noted in the name of several of the vasculitides. It is not known whether specific properties of the microenvironment in the blood vessel wall or the immediate surroundings of blood vessels contribute to granuloma formation and, in some cases, generation of multinucleated giant cells. Granulomas provide a specialized niche to optimize macrophage–T cell in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 165 publications
(180 reference statements)
0
55
0
3
Order By: Relevance
“…Granuloma formation is thought to be initiated by small aggregates of neutrophils surrounding necrotic areas (microabscess). [85][86][87] In GPA, granulomatous inflammation can be found in several affected organs, a feature not found in MPA. 88 Granuloma formation can be found in both PR3-ANCA-positive patients and MPO-ANCA-positive patients diagnosed with GPA.…”
Section: Histopathologic Featuresmentioning
confidence: 99%
“…Granuloma formation is thought to be initiated by small aggregates of neutrophils surrounding necrotic areas (microabscess). [85][86][87] In GPA, granulomatous inflammation can be found in several affected organs, a feature not found in MPA. 88 Granuloma formation can be found in both PR3-ANCA-positive patients and MPO-ANCA-positive patients diagnosed with GPA.…”
Section: Histopathologic Featuresmentioning
confidence: 99%
“…By definition, granulomas are organized lymphoid microstructures, composed of two major cell populations: macrophages, sometimes called histiocytes, which may fuse to form giant cells and CD4 T cells. Granulomas have been implicated in containment of intracellular bacterial infections and difficult-to-digest irritants, but convincing data implicating either in the pathogenesis of GCA are missing (5, 6). …”
Section: Introductionmentioning
confidence: 99%
“…14,15 Previous studies have demonstrated that CD4 + T cells are considered as the key participant in silicosis, and Th1/Th2 cells participate in the pathogenesis of silicosis. 16,17 DCs are the most efficient APCs that can activate both T cells and B cells and thus, they act as a bridge between innate and adaptive immunity. [18][19][20][21] Besides, DCs also have the ability to inuence T cell polarization via three ways: (i) antigen presentation, (ii) co-stimulatory molecule expression, and (iii) direct contribution by DCs to the immediate cytokine milieu that directs the resultant Th cell response.…”
Section: Introductionmentioning
confidence: 99%